2020
DOI: 10.3390/cells9030778
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Adsorption on Electrospun Synthetic Vascular Grafts Attracts Endothelial Progenitor Cells and Promotes Endothelialization in Dynamic In Vitro Culture

Abstract: Appropriate mechanical properties and fast endothelialization of synthetic grafts are key to ensure long-term functionality of implants. We used a newly developed biostable polyurethane elastomer (TPCU) to engineer electrospun vascular scaffolds with promising mechanical properties (E-modulus: 4.8 ± 0.6 MPa, burst pressure: 3326 ± 78 mmHg), which were biofunctionalized with fibronectin (FN) and decorin (DCN). Neither uncoated nor biofunctionalized TPCU scaffolds induced major adverse immune responses except fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 132 publications
(180 reference statements)
2
27
0
Order By: Relevance
“…They found increased endothelialization for the modified BNC constructs in comparison to uncoated constructs and concluded that the RGD modification was the key factor for the improved cell adherence. We observed similar behaviors of EPCs on our fibronectin-coated grafts, which is also in line with the literature, as it is known that fibronectin coating of vascular grafts induces the homing of CD34+ endothelial progenitor cells [ 87 ] and promotes VEGF-induced CD34 + cell differentiation into ECs [ 88 ]. Consistent with that, our EPCs were characterized as CD34 + by FACS.…”
Section: Discussionsupporting
confidence: 90%
“…They found increased endothelialization for the modified BNC constructs in comparison to uncoated constructs and concluded that the RGD modification was the key factor for the improved cell adherence. We observed similar behaviors of EPCs on our fibronectin-coated grafts, which is also in line with the literature, as it is known that fibronectin coating of vascular grafts induces the homing of CD34+ endothelial progenitor cells [ 87 ] and promotes VEGF-induced CD34 + cell differentiation into ECs [ 88 ]. Consistent with that, our EPCs were characterized as CD34 + by FACS.…”
Section: Discussionsupporting
confidence: 90%
“…Adsorbing FN onto or absorbing it into cell scaffolds is a strategy extensively used to promote cell attachment. [39][40][41][42] Recent reports show that recombinant engineered FN fragments can be even more efficient than full-length FN at promoting cell attachment and growth. 43,44 Licht et al 38 engineered an injectable PEG-based hydrogel functionalized with a recombinant FN fragment (FNIII9*-10/12-14) that contained cell adhesive motifs and a growth factor domain for nerve tissue regeneration.…”
Section: Syps Functionalization To Promote Cell Attachment and Proliferationmentioning
confidence: 99%
“…Adhesive Proteins: To inhibit blood coagulation and strengthen cell affinity for ECs/EPCs, cell-adhesive proteins have been incorporated into the vascular biomaterials. Among these proteins, collagen, [182] gelatin, [183] fibronectin, [184] and keratin [185] can effectively improve endothelialization and vascular remodeling of the polymeric vascular grafts. However, proteins usually exhibit low stabilities and possess complex structure relative to peptides, which may limit their biomedical application.…”
Section: Physical Approachmentioning
confidence: 99%